(3cJGH GdJUQjas - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bO JbOe dfG bHd cJGHfG cJH cKjQI ai Yde GdehGRjf hYdefG ajgG hLhO faYkG hPdc Cf GdOdjd YdjgG ai GdcejI Yde BNQ s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hbO GSJhajfG Pdc ai cJGHfG GdeYQha HNhGU GdMLQ GdcQje ef GdeGFI hGKfi YTQ cJGH ef CMH Cf jYde Pdc hgh PQ GdaGjOI GdYXjeI hGdefaYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs